ReFocus. exile, displacement and the stateless moving image - Fatehrad, Azadeh (ReFocus: the international directors series., 2020)
In this - the first English-language book to reflect on his work and its implications for creativity in the diasporic conditions of urban displacement - a range of international scholars provide a comprehensive account of Shahid Saless's films and production methods.